2021
DOI: 10.1038/s41467-021-21992-w
|View full text |Cite
|
Sign up to set email alerts
|

Favipiravir antiviral efficacy against SARS-CoV-2 in a hamster model

Abstract: Despite no or limited pre-clinical evidence, repurposed drugs are massively evaluated in clinical trials to palliate the lack of antiviral molecules against SARS-CoV-2. Here we use a Syrian hamster model to assess the antiviral efficacy of favipiravir, understand its mechanism of action and determine its pharmacokinetics. When treatment is initiated before or simultaneously to infection, favipiravir has a strong dose effect, leading to reduction of infectious titers in lungs and clinical alleviation of the dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
136
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(148 citation statements)
references
References 42 publications
11
136
1
Order By: Relevance
“…In this absence of effective anti-COVID-19 therapy, some researchers have suggested the repurposing of the known potent antiinfluenza drug favipiravir (chemically, it is a purine nucleoside analog; approved for medical use in Japan since 2014; Fig. 2 ) to counteract the novel COVID-19 (Shiraki and Daikoku 2020 ; Dong et al 2020 ; Łagocka et al 2021 ; Driouich et al 2021 ). Previous studies identified viral RNA-dependent RNA polymerase (RdRp) as a potential drug target in COVID-19 treatment due to its crucial role in SARS-CoV-2 replication and transcription (i.e., in the virus life cycle) (Zhang and Tang 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this absence of effective anti-COVID-19 therapy, some researchers have suggested the repurposing of the known potent antiinfluenza drug favipiravir (chemically, it is a purine nucleoside analog; approved for medical use in Japan since 2014; Fig. 2 ) to counteract the novel COVID-19 (Shiraki and Daikoku 2020 ; Dong et al 2020 ; Łagocka et al 2021 ; Driouich et al 2021 ). Previous studies identified viral RNA-dependent RNA polymerase (RdRp) as a potential drug target in COVID-19 treatment due to its crucial role in SARS-CoV-2 replication and transcription (i.e., in the virus life cycle) (Zhang and Tang 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Six dosing groups were tested: a) two prophylaxis groups treated with doses of 2 mg/kg or 200 mg/kg, b) two post-treatment groups treated with doses of 2 mg/kg or 200 mg/kg, and two control groups that were infected or not infected. Disease in hamsters following SARS-CoV-2 infection was transient peaking around day 3-4 post-infection with no clinical signs 17 . Consistent with this observation, no clinical symptoms or weight loss was evident in any group throughout the study (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 97%
“…Having shown in vitro efficacy and determined the IC50 values, we next determined the efficacy of probenecid in the hamster model regarded as a preclinical model of SARS-CoV-2 disease with hamsters having self-limiting pneumonia 17,18 . We examined hamsters infected with SARS-CoV-2 and treated them with probenecid for either 24h before infection (prophylaxis) or 48h post-infection (post-treatment).…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports from the RECOVERY and REMAP-CAP trials showed that treatment with tocilizumab led to lower mortality across patients with different disease severities [ 18 , 19 ]. Two studies using a hamster model of SARS-CoV-2 infection have shown a modest antiviral effect of favipiravir [ 20 , 21 ]. In a retrospective study from 2 hospitals in SA, use of favipiravir was associated with accelerated discharge rate and less progression to mechanical ventilation, but no overall mortality benefits [ 22 ].…”
Section: Discussionmentioning
confidence: 99%